2012
DOI: 10.1901/jaba.2012.45-419
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Video Modeling With Voiceover Instruction on Accurate Implementation of Discrete‐trial Instruction

Abstract: The present study replicates and extends previous research on the use of video modeling (VM) with voiceover instruction to train staff to implement discrete-trial instruction (DTI). After staff trainees reached the mastery criterion when teaching an adult confederate with VM, they taught a child with a developmental disability using DTI. The results showed that the staff trainees' accurate implementation of DTI remained high, and both child participants acquired new skills. These findings provide additional su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
68
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 4 publications
10
68
1
1
Order By: Relevance
“…First, two studies included video modeling within a BST package: Lavie and Sturmey (2002) used video modeling with instructions, rehearsal, and feedback; Nosik et al (2013) used computer-based instruction with video modeling, instructions, and feedback. Second, four studies demonstrated the efficacy of video modeling alone in improving staff implementation of behavioral procedures (Catania et al, 2009;Collins et al, 2009;Moore & Fisher, 2007;Vladescu et al, 2012). Finally, two studies also found that video modeling alone was effective (i.e., produced approximately 80% procedural accuracy) but that the subsequent delivery of performance feedback (DiGennaro-Reed et al, 2010) or video-based feedback (Nosik & Williams, 2011) resulted in further improvements to staff performance (i.e., produced approximately 100% procedural accuracy).…”
Section: Research On Video Modelingmentioning
confidence: 98%
See 2 more Smart Citations
“…First, two studies included video modeling within a BST package: Lavie and Sturmey (2002) used video modeling with instructions, rehearsal, and feedback; Nosik et al (2013) used computer-based instruction with video modeling, instructions, and feedback. Second, four studies demonstrated the efficacy of video modeling alone in improving staff implementation of behavioral procedures (Catania et al, 2009;Collins et al, 2009;Moore & Fisher, 2007;Vladescu et al, 2012). Finally, two studies also found that video modeling alone was effective (i.e., produced approximately 80% procedural accuracy) but that the subsequent delivery of performance feedback (DiGennaro-Reed et al, 2010) or video-based feedback (Nosik & Williams, 2011) resulted in further improvements to staff performance (i.e., produced approximately 100% procedural accuracy).…”
Section: Research On Video Modelingmentioning
confidence: 98%
“…Researchers have used video modeling to teach staff or teachers a variety of skills, such as conducting a paired-stimulus preference assessment (Lavie & Sturmey, 2002), conducting a functional analysis of problem behavior (Moore & Fisher, 2007), implementing components of a behavior intervention plan (DiGennaro-Reed, Codding, Catania, & Maguire, 2010), teaching clients a problem-solving strategy (Collins, Higbee, & Salzberg, 2009), and delivering discrete-trial training (DTT; Catania et al, 2009;Nosik & Williams, 2011;Nosik, Williams, Garrido, & Lee, 2013;Vladescu, Carroll, Paden, & Kodak, 2012). Using multiple-baseline designs across participants, the researchers in eight published studies demonstrated effects of training with video models compared to baseline conditions that included written or verbal explanations, written protocols, data sheets, or pre-training with modeling and role-play (no feedback).…”
Section: Research On Video Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…VM has been used in the SPA staff training literature as one component of a comprehensive training package (Bishop and Kenzer 2012;Lavie and Sturmey 2002) and has been used to successfully train staff to implement functional analysis methodology (Moore and Fisher 2007), problem-solving interventions (Collins et al 2009), and discrete-trial instruction (Catania et al 2009;Vladescu et al 2012). VM is often combined with voiceover instruction to increase the saliency of certain portions of the video, and may be useful in settings where access to qualified supervisors may be limited (e.g., rural areas).…”
mentioning
confidence: 99%
“…In these studies, video modeling with voiceovers that described the critical components of DTT was effective for teaching direct service staff to implement DTT with a high degree of integrity during role play with the experimenter (Catania, Almeida, Liu-Constant, & Digennaro, 2009 ) and during teaching sessions with children (Vladescu, Carroll, Paden, & Kodak, 2012 ).…”
Section: Alternative Modalitiesmentioning
confidence: 99%